24.8k views
5 votes
Use the method of completing the square to transform the quadratic equation into the equation form (x + p)2 = q. -4 + 4x + x2 = 0

1 Answer

2 votes

Answer:

(x + 2)² = 8

Explanation:

To complete the square, write the equation standard form.

-4 + 4x + x² = 0

x² + 4x - 4 = 0

Take the middle term 4x and divide the coefficient in 2 and square it. Here it is 4/2 = 2. 2² = 4. Add 4 to both sides.

x² + 4x + 4 - 4 = 0 + 4

(x + 2)² - 4 = 4

(x + 2)² = 8

User Railsbox
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.